The Effect Of Work Duration And Work Porture On Low Back Pain In Weavers In Troso Village Rt.1 RW.2 Pecangaan Subdistrict Jepara District - Susilo Budi Pratama; Bima Rizki Aditya Putra; Chamim Faizin (Sean Institute, 2023)
Low Back Pain (LBP) is lower back pain originating from the spine. Low back pain is one of the complaints that can lead to decreased human productivity, 80% of the population in industrialized countries have felt low back pain, the percentage increases with the age of the patient. Based on basic health research in 2018, the prevalence of low back pain in Indonesia varies from 7.6% to 37%. To analyze the effect of work duration and work posture on low back pain in weavers in Troso Village RT.1 RW.2. This study used quantitative methods in the form of analytic observations with a cross sectional approach. The research was conducted on August 26-30, 2023. The sample in this study were weavers in Troso Village RT.I RW.2, Pecangaan District, Jepara Regency. Sampling using consecutive sampling technique with regard to inclusion and exclusion criteria. The number of samples obtained was 60 people. The analysis used was univariate analysis using descriptive frequency, while bivariate analysis used the spearman rank correlation test. Univariate analysis showed that the majority of respondents with work duration> 7 hours as many as 44 people (73.3%), the results of the RULA work questionnaire category need further investigation, and changes are made if necessary posture as many as 31 people (51.7%), and suffered from LBP as many as 46 people (76.7%). In the bivariate analysis of the effect of work duration on low back pain, the Spearman rank correlation test value p = 0.000 (p <0.05) and the value of r = +0.648. On the effect of work posture on low back pain, the value of the spearman rank correlation test p = 0.021 (p <0.05) and the value of r = +0.297. There is a strong influence between work duration and low back pain in weavers in Troso Village RT.1 RW.2. There is a weak influence between work posture on low back pain in weavers in Troso Village RT.1 RW.2.